Impact of Interprofessional Education Collaboration in Attitudes, Skills, and Behavior among Medical Students in Asia: A Narrative Review - Prakoeswa, Flora Ramona Sigit; Pramuningtyas, Ratih; Risanti, Erika Diana; Prayitno, Harun Joko; Sari, Winda Atika (CV. Publikasi Indonesia, 2025)
Interprofessional education (IPE) involves collaboration among various fields within the healthcare system to achieve optimal health outcomes. IPE reduces gaps between health professionals from diverse backgrounds, fostering teamwork and effective collaboration. Early integration of IPE into medical curricula is essential to equip students with the knowledge, skills, and attitudes required for collaborative healthcare practices, ultimately improving patient care, reducing medical errors, and enhancing healthcare service quality. This review investigates the impact of early exposure to IPE on the skills, attitudes, and collaborative abilities of medical students in Asia. The goal is to assess whether early introduction fosters professionalism and effective interprofessional collaboration. Literature searches were conducted using Google Scholar and PubMed with appropriate keywords (interprofessional education, collaboration, medicine, and education). Articles were assessed for evidence-based relevance to the global health system, and those with cultural, racial, or religious biases were excluded. Review writing review based on 40 sources (journals, books, or WHO guidelines) that meet the criteria and keywords. Findings suggest that early engagement with IPE promotes positive attitudes, teamwork, and leadership skills among medical students. However, concerns remain regarding insufficient genuine interprofessional collaboration and potential declines in student attitudes without proper implementation. The early introduction of IPE has the potential to cultivate professionalism and collaborative skills among medical students in Asia. This review provides a foundation for encouraging the inclusion of IPE in medical curricula to improve interprofessional collaboration and healthcare outcomes.